Professors´ Perceptions of the Challenges of Teaching English at a Costa Rican Public University (Revista Rupturas, 2025)
This phenomenological study addresses the challenges faced by professors in teaching the course LM1001-Integrated English I at the Caribbean Campus of the University of Costa Rica. The challenges identified include the disparity in students' language proficiency levels, which affects the quality and efficiency of the educational process. In addition, the lack of adequate filters to evaluate students' language skills upon entering the course is highlighted, generating an additional burden for teachers. The proposed solutions include the implementation of diagnostic tests, self-assessment systems and the use of technology in classroom activities to improve the teaching and learning of English.
Keywords: professors´ perception; English teaching; desertion; challenges